Biochemical characterization of an isolated 50 kDa beta-glucosidase from the thermophilic fungus Myceliophthora thermophila M.7.7 - Bonfá, Emily Colferai [UNESP] (2018)
This study characterized a 50 kDa β-glucosidase (BGL50) produced by the thermophilic fungus Myceliophthora thermophila M.7.7 in solid state cultivation using a mixture of (1:1) sugarcane bagasse and wheat bran. The crude extract zymogram showed two isoforms of β-glucosidase with approximately 50 and 200 kDa, which were separated by gel filtration chromatography. The characterization of BGL50 showed optimum activity at 60 °C and pH 5.0 when 4-nitrophenyl β-D-glucopyranoside (pNPG) was used as the substrate, whereas when using cellobiose, the highest activity was observed at 50 °C and pH 4.5. Several ions and reagents produced different effects on the enzyme activity depending on the substrate and there was complete inhibition with Cu2+ and Fe3+ for both substrates. In addition, nine phenolic compounds showed no inhibitory effects on the enzyme, a significant feature since β-glucosidase is used for the saccharification of lignocellulosic biomass that generates several phenolic compounds. Kinetic studies revealed competitive inhibition by glucose when pNPG was used, with a Ki value of 1.5 mM and a significantly lower Km (0.52 mM) than for cellobiose (8.50 mM). The thermodynamic parameters showed that BGL50 is very stable at 60 °C displaying a half-life of 855.6 min but it is easily denatured above this temperature. The results emphasize the importance of investigating potential β-glucosidases based on cellobiose instead of using only pNPG since, in the industrial process, the enzyme will act on this natural substrate. In addition, understanding the thermostability of the enzyme is an important contribution to enzyme technology.